Implementation Of Problem Based Learning Method In Manual Harmony Course At The Music Education Study Program Of FSP ISI Yogyakarta (Universitas Negeri Semarang, 2022)
The materials of Manual Harmony course are a combination of harmony science class materials and basic piano practice class materials. The subject is aimed to train students to play four-part harmony on pianos and accompany a melody using the correct chords. Regarding the lectures, it is necessary to modify the teacher-centered to student-centered method to help students better understand the materials. It is also expected that the student-centered method will give the students opportunities to explore their skills and express their ideas during classes. The aim of this research was to improve students’ skills in playing four-part harmony correctly, accompanying songs or melodies with correct chords, building problem solving as well as thinking skills in Harmony Manual class which will benefit them in the future. The researcher implemented qualitative method. The data were obtained from Manual Harmony class at the Undergraduate Program of Music Education FSP ISI Yogyakarta. They were taken from literary studies, observations, and interviews. The data were then analyzed through data reduction, data display, and conclusion drawing. The findings revealed that problem-based learning method was highly effective in teaching Manual Harmony subject.